Ethical rationales for past and present military medical practices. Issue 4 (7th August 2019) - Howe, Edmund
Abstract : This paper reviews changes in the ethical challenges that have arisen in military medicine over the past four decades. This includes the degree, if any, to which providers during the Vietnam conflict have carried out what we now refer to as harsh interrogation measures in an attempt to extract information from captured enemy soldiers, the extent, if any, to which the USA used medicine as a means to try to win over the hearts and minds of civilians in occupied territory and how providers should treat service members who return from the front with combat fatigue. An issue that arose during the first Gulf War in 1991 is discussed, namely US service persons being required to take botulism vaccine without their consent. Finally, present challenges are discussed including interrogation measures such as waterboarding and the ethical issues posed in the recent past by the exclusion of gay service members and those posed presently by the inclusion of transgender members. Two ethical values are suggested that have remained constant, namely giving priority to the individual needs of service personnel over those of the unit when there are no urgent combat needs and the reliance on individual virtue when what they should do is morally unclear.